The entry inhibitor Myrcludex-B efficiently blocks intrahepatic virus spreading in humanized mice previously infected with hepatitis B virus - Volz, Tassilo; Allweiss, Lena; ḾBarek, Mounira Ben; Warlich, Michael; Lohse, Ansgar W.; Pollok, Jörg M.; Alexandrov, Alexander; Urban, Stephan; Petersen, Jörg; Lütgehetmann, Marc; Dandri, Maura (Journal of hepatology, 2013)
Background & Aims - Currently approved antivirals rarely cure hepatitis B virus (HBV) infection. Therefore additional therapeutic strategies interfering with other viral replication steps are needed. Using synthetic lipopeptides derived from the HBV envelope protein, we previously demonstrated prevention of de novo HBV infection in vivo. We aimed at investigating the ability of the lipopeptide Myrcludex-B to block HBV spreading post-infection. - Methods - uPA/SCID mice reconstituted with human hepatocytes were infected with HBV. Daily subcutaneous Myrcludex-B administration was initiated either 3days, 3weeks or 8weeks post HBV inoculation. Viral loads were quantitated in serum and liver, and visualized by immunohistochemistry. - Results - Myrcludex-B efficiently prevented viral spreading from the initially infected human hepatocytes, as demonstrated by the lack of increase in viremia, antigen levels and amount of HBcAg-positive human hepatocytes determined 6weeks after treatment. Myrcludex-B efficiently blocked HBV dissemination also when treatment was started in the ramp-up phase of infection, in mice displaying moderate levels of circulating virions (median 3×106HBV DNA copies/ml). Notably, after 6weeks of treatment, not only the amount of HBcAg-positive hepatocytes, but also intrahepatic cccDNA loads, remained comparable to values found in mice sacrificed 3weeks post-infection. In none of the experimental settings, drug administration affected human hepatocyte half-life or altered virion productivity. - Conclusions - Myrcludex-B efficiently not only prevented HBV spreading from infected human hepatocytes in vivo, but also hindered amplification of the cccDNA pool in initially infected hepatocytes. Administration of an entry inhibitor, possibly used in combination with current HBV drugs, may improve patients’ treatment outcome.